Hubungan Antara Dukungan Sosial dan Stres Akademik pada Mahasiswa Psikologi Universitas Negeri Malang - Rahmah, Amelia Dwi; Hidayat, Muhammad Faisal; Zahra, Yesenia Salsabila Az; Pramestiti, Yustisia; Vardia, Melly Amalia (Flourishing Journal, 2025)
College students often experience academic stress due to the excessive pressure they are under during their studies. Providing social support can reduce the adverse effects of academic stress. The purpose of this study was to examine the relationship between academic stress and social support of students of the Faculty of Psychology, State University of Malang. The study used a correlational quantitative method. The data collection technique used, namely purposive sampling with the sample of this study amounted to 65 subjects. Data were collected through the use of PSS (Perceived Stress Scale) and MSPSS (Multidimensional Scale of Perceived Social Support) scales. The data were then analyzed by a correlation test using the Pearson product-moment technique. The results of data analysis found that the significance of p = 0.046 (p < 0.05), which states that the alternative hypothesis is accepted; the correlation test results state that there is a relationship between social support and academic stress. The correlation coefficient value of r = -0.211 states that there is a negative relationship between the two variables. this relationship states that the higher the level of social support obtained by individuals, the lower the level of academic stress experienced. AbstrakMahasiswa perguruan tinggi kerap kali mengalami stres akademik akibat tekanan berlebih yang didapatkan selama menjalani studi. Memberikan dukungan sosial dapat mengurangi dampak buruk dari stres akademik. Tujuan dari penelitian ini untuk menguji hubungan terkait stres akademik dengan dukungan sosial mahasiswa Fakultas Psikologi Universitas Negeri Malang. Penelitian menggunakan metode kuantitatif korelasional. Teknik pengumpulan data yang digunakan, yaitu purposive sampling dengan sampel penelitian ini berjumlah 65 subjek. Data dikumpulkan melalui penggunaan skala PSS (Perceived Stress Scale) dan MSPSS (Multidimensional Scale of Perceived Social Support). Data kemudian dianalisis dengan uji korelasi menggunakan teknik pearson product moment. Hasil analisa data ditemukan bahwa signifikansi p = 0,046 ( p < 0,05) yang menyatakan bahwa hipotesis alternatif diterima, hasil uji korelasi menyatakan terdapat hubungan antara dukungan social dan stress akademik. Nilai koefisien korelasi sebesar r = -0,211 menyatakan terdapat hubungan negative pada kedua variable, hubungan ini menyatakan semakin tinggi tingkat dukungan sosial yang didapatkan oleh individu, maka akan semakin rendah tingkat stres akademik yang dialami.